Evaluation of Information Technology Governance in the University Admissions Unit - Reski, Chatherina; Nisa, Zapiratun; Sabrila, Trifebi Shina; Latif, Abdul; Lindawati, Ratna (LPPM Universitas Sari Mulia, 2024)
Information Technology (IT) governance plays a crucial role in ensuring that IT resources align with organizational goals, optimize performance, and minimize risks. This study evaluates IT governance maturity in the Marketing department of Universitas Sari Mulia (UNISM) using the COBIT 5 framework, focusing on two process domains: EDM04 (Ensure Resource Optimization) and APO08 (Manage Relationships). The research methodology includes surveys and direct interviews to assess the current maturity level and identify gaps between existing and expected conditions. The evaluation results indicate that EDM04 has an average maturity level of 2.33 (Managed), while APO08 is at 3.2 (Established). The gap analysis shows that both domains require further improvements, with EDM04 having a gap of 2.67 and APO08 a gap of 1.8. These findings highlight the need for enhanced IT governance practices to optimize resource management and stakeholder relationships. The study provides recommendations for improving IT governance maturity in UNISM Marketing department, ensuring a more structured and efficient IT management process.